Architectural Filth and the Heroic Passivism of Farhadi's Salesman - Vahdat, Vahid (Interiority, 2021)
Architecture in Asghar Farhadi’s The Salesman (2016) is not a mere passive backdrop to an otherwise unaffected narrative; it is an autonomous agent that takes part in the events that unfold, complicates the narrative, and even occasionally defies the ideological position of the film. By analysing interior spaces, architectural elements, urban infrastructure, and maintenance practices, I suggest that 1) the fluid visual boundaries of Farhadi’s spatial settings are instrumental in blurring the borders of truth and morality—themes that are central to his film; 2) the ontological study of architecture, from the moment of excavation to its ultimate fracture/failure serves as a pathological medium to study the troubled masculinity of contemporary Iranian society; 3) spatial infrastructure, as the materialised memory of the film’s determinism, prophetically hints at the inevitable tragedy that awaits. The architectural analysis of The Salesman empowers the audience with additional tools to reflect upon questions of masculinity and determinism. Architecture-as-a-reflection personifies the social filth that cannot be decontaminated through vain beautification strategies. Architecture-as-a-stage reflects the temporality of space and its incidental existence vis-à-vis the dominating presence of infrastructural facilities. Architecture-as-a-confinement embodies the oppressive nature of a society in which restriction, surveillance, and control are imposed upon its residents.